Kritik Unsur Kearifan Lokal pada Label Kemasan Kopi Van Dillem Trenggalek - Renzy Ayu Rohmatillah (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2022)
The visual meaning of Van Dillem’s coffee packaging labels is examined in this researh. This coffee is a product from Trenggalek. This product’s packaging label was examined to determine how the visual meaning and whether it correlates with the Trenggalek's local wisdom. Literature analysis and observation are the data collection methods used in this research. The four stages of Feldman’s theory of art criticism—description, analysis, interpretation, and evaluation—are used in this research. Van Dillem coffee carries the name of the region to be exposed to the larger population as a representative product of Trenggalek. Local product packaging labels’ graphic components might reflect regional traits to draw attention to the region of production. The findings indicate that colonialism is visually represented on the coffee product packaging label. The history of coffee product manufacturing in Trenggalek is connected to this aspect of colonialism.